Analisis Hadist Tarbawi tentang Pendidikan Diri dan Pendidikan Anak - Hafid Huddin, Moh; Dwi Nuriana, Eva; Sintiya (Jumper: Journal of Educational Multidisciplinary Research, 2025)
Hadith is the second guideline in Islam. There are many hadiths of the Prophet related to education, mainly self-education and children's education. This article examines self-education and children's education from a hadith perspective. The research method used uses library research methods. The data sources for this research come from the authentic hadith books of Bukhari and Muslim as primary data sources, as well as relevant journal articles as secondary data sources. The collected data was then analyzed using content analysis. The research results show that self-education includes moral development, religious understanding, and awareness of humans' role as God's caliphs on earth. Meanwhile, children's education starts from an early age by instilling religious values, ethics and discipline.